Polyamines in Pollen: From Microsporogenesis to Fertilization - Aloisi, Iris; Cai, Giampiero; Serafini-Fracassini, Donatella; Del Duca, Stefano (Frontiers in Plant Science, 2016)
The entire pollen life span is driven by polyamine (PA) homeostasis, achieved through fine regulation of their biosynthesis, oxidation, conjugation, compartmentalization, uptake, and release. The critical role of PAs, from microsporogenesis to pollen–pistil interaction during fertilization, is suggested by high and dynamic transcript levels of PA biosynthetic genes, as well as by the activities of the corresponding enzymes. Moreover, exogenous supply of PAs strongly affects pollen maturation and pollen tube elongation. A reduction of endogenous free PAs impacts pollen viability both in the early stages of pollen development and during fertilization. A number of studies have demonstrated that PAs largely function by modulating transcription, by structuring pollen cell wall, by modulating protein (mainly cytoskeletal) assembly as well as by modulating the level of reactive oxygen species. Both free low-molecular weight aliphatic PAs, and PAs conjugated to proteins and hydroxycinnamic acids take part in these complex processes. Here, we review both historical and recent evidence regarding molecular events underlying the role of PAs during pollen development . In the concluding remarks, the outstanding issues and directions for future research that will further clarify our understanding of PA involvement during pollen life are outlined.